Investigation of glucose-modified liposomes using polyethylene glycols with different chain lengths as the linkers for brain targeting - Xie F (Dove Medical Press, 2012)
Fulan Xie1,*, Nian Yao1,*, Yao Qin1, Qianyu Zhang1, Huali Chen1, Mingqing Yuan1, Jie Tang1, Xiankun Li1, Wei Fan1, Qiang Zhang2, Yong Wu1, Li Hai1, Qin He11Key Laboratory of Drug Targeting and Drug Delivery Systems, West China School of Pharmacy, Sichuan University, Chengdu, People's Republic of China; 2State Key Laboratory of Natural and Biomimetic Drugs, School of Pharmaceutical Sciences, Peking University, Beijing, People's Republic of China *These authors contributed equally to this workBackground: An intimidating challenge to transporting drugs into the brain parenchyma is the presence of the blood–brain barrier (BBB). Glucose is an essential nutritional substance for brain function sustenance, which cannot be synthesized by the brain. Its transport primarily depends on the glucose transporters on the brain capillary endothelial cells. In this paper, the brain-targeted properties of glucose-modified liposomes using polyethylene glycols with different chain lengths as the linkers were compared and evaluated to establish an optimized drug-delivery system.Methods: Coumarin 6-loaded liposomes (GLU200-LIP, GLU400-LIP, GLU1000-LIP, and GLU2000-LIP) composed of phospholipids and glucose-derived cholesterols were prepared by thin-film dispersion-ultrasound method. The BBB model in vitro was developed to evaluate the transendothelial ability of the different liposomes crossing the BBB. The biodistribution of liposomes in the mice brains was identified by in vivo and ex vivo nearinfrared fluorescence imaging and confocal laser scanning microscopy and further analyzed quantitatively by high-performance liquid chromatography.Results: Glucose-derived cholesterols were synthesized and identified, and coumarin 6-loaded liposomes were prepared successfully. The particle sizes of the four types of glucose-modified liposomes were around or smaller than 100 nm with a polydispersity index less than 0.300. GLU400-LIP, GLU1000-LIP, and GLU2000-LIP achieved higher cumulative cleared volumes on BBB model in vitro after 6 hours compared with GLU200-LIP (P < 0.05) and were significantly higher than that of the conventional liposome (P < 0.001). The qualitative and quantitative biodistribution results in the mice showed that the accumulation of GLU1000-LIP in the brain was the highest among all the groups (P < 0.01 versus LIP).Conclusion: The data indicated that GLU400-LIP, GLU1000-LIP, and GLU2000-LIP all possess the potential of brain targeting, among which GLU1000-LIP, as a promising drug-delivery system, exhibited the strongest brain delivery capacity.Keywords: glucose, polyethylene glycols, liposome, BBB, brain-targeted